Meta-Analysis: Application of Health Belief Model Theory on Covid-19 Vaccine Acceptance - Tursina, Elsa; Rahardjo, Budhi; Nugroho, Farid Setyo (GLOBAL HEALTH SCIENCE GROUP, 2024)
The Health Belief Model (HBM) helps in understanding health-related behaviors and is used to explore factors that influence the acceptance of COVID-19 vaccines. This exploration serves as the basis for designing more effective intervention programs to increase vaccine acceptance, both for COVID-19 and future vaccination programs. This study aims to analyze and estimate the impact of applying the Health Belief Model on the acceptance of COVID-19 vaccines. Methods: This study is a meta-analysis using the PICO model. Population: adults. Intervention: high perceived susceptibility, high perceived severity, high perceived benefits. Comparison: low perceived susceptibility, low perceived severity, low perceived benefits. Outcome: acceptance of COVID-19 vaccination. The research data was sourced from Google Scholar, ScienceDirect, and PubMed, using keywords “Health Belief Model” AND “HBM” AND “Vaccine COVID-19 Acceptance” OR “Receive” AND “Vaccine COVID-19 Hesitancy”. The inclusion criteria for articles in the meta-analysis were articles published between 2020 and 2022 in English. Analysis was performed using the RevMan 5.4 application. Results: A meta-analysis was conducted on 15 cross-sectional studies from Asia and Europe with a total sample size of 19,814 people. High perceived susceptibility (aOR= 1.28; 95% CI= 1.10 to 1.49; p= 0.001), high perceived severity (aOR= 1.24; 95% CI= 1.04 to 1.48; p= 0.020), and high perceived benefits (aOR= 2.64; 95% CI= 1.73 to 4.02; p<0.001) towards COVID-19 were found to increase the acceptance of COVID-19 vaccination, and these results were statistically significant. Conclusion: High perceived susceptibility, high perceived severity, and high perceived benefits towards COVID-19 increase the acceptance of COVID-19 vaccination.